1955
DOI: 10.1002/aja.1000960305
|View full text |Cite
|
Sign up to set email alerts
|

The influence of vitamin A on the epidermis

Abstract: TWELVE FIQURESSabella, Bern and Kahn ( '51) demonstrated that vitamin A dissolved in sesame oil, applied topically to the dorsal epidermis of castrated mature feimale rats f o r 10 days, resulted in a significant increase in thickness of the whole epidermis (less the stratum corneum) and of the stratum granulosum alone over both that of sesame oil-treated and of untreated controls. Effects on the stratum corneum were indicated, including occasional parakeratosis, but were not possible to quantify. It was concl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1957
1957
1986
1986

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…I t also delays or inhibits the oestrogen-induced keratinisation in cultures of rat and mouse vagina (Kahn, 1954;Lasnitzki, 1961). The effect on skin seems to be species-dependent; thus topical application of the vitamin induced a hypertrophy of mouse and rat epidermis but failed to influence keratinisation (Bern et al, 1955;Lawrence and Bern, 1958).…”
mentioning
confidence: 99%
“…I t also delays or inhibits the oestrogen-induced keratinisation in cultures of rat and mouse vagina (Kahn, 1954;Lasnitzki, 1961). The effect on skin seems to be species-dependent; thus topical application of the vitamin induced a hypertrophy of mouse and rat epidermis but failed to influence keratinisation (Bern et al, 1955;Lawrence and Bern, 1958).…”
mentioning
confidence: 99%
“…150 IU vita min A daily, has no different effect than the oil vehicle. However, as vitamin A is known to produce epithelial hyperplasia in vivo [Bern et al, 1955] and in vitro [Lasnitzki, 1961], the hyperplasia found in this experimental group was explicable and provided a further useful vari able with respect to the Langerhans cell population.…”
Section: Discussionmentioning
confidence: 99%
“…These changes included decreased keratinization, mucoid metaplasia, epithelial hyperplasia, disorientation of the basal layer, and increased mitoses (Bern et al, 1955;J ackson and F e l l , 1963; L a w r en c e and Ber n , 1958 and1960;R eiss and C am pbell, 1954;Rothberg , 1967).…”
Section: Discussionmentioning
confidence: 99%